Feminismo para 99% em Porto Alegre : o caráter transnacional dos protestos de 08 de março de 2017 - Hammarstron, Natane Flores (2020)
The year 2016 was marked by feminist uprisings. In Argentina, the Ni Una a Menos movement denounced and charged measures after brutal murders of women. In Poland, women dressed in black and took to the streets to overturn a bill that promised to ban abortion altogether. Protests and women's strikes spread to neighboring countries; a major international women's strike was planned for March 8, 2017, marking Women's Day. The Americans released a letter calling for the mobilizations of that day and inviting the construction of an anticapitalist-based feminism for 99%. The aim of this research aims to understand how the transnational context influenced the protests of International Women's Day in 2017 in Porto Alegre and how the local context provided a bridge between frameworks. The methodology implies documental analysis of the letter, pamphlets and etc. Ten interviews were conducted with activists from collectives working in the construction of the 8M, in Porto Alegre, this year. The action through collective action networks is among the forms of organization of the feminist movement. Through the theory of confrontation, concepts such as coalition of events, global frame, repertoire of action and diffusion are paramount.